Smartphone sensors for evaluating COVID-19 fear in patients with cancer: a prospective study - Kasputytė, Gabrielė; Jenciūtė, Gabrielė; Šakinis, Nerijus; Bunevičienė, Inesa; Korobeinikova, Erika; Vaitiekus, Domas; Inčiūra, Arturas; Jaruševičius, Laimonas; Bunevičius, Romas; Krikštolaitis, Ričardas; Krilavičius, Tomas; Juozaitytė, Elona; et al. (Frontiers in Public Health, 2024)
Objective: To analyze the association of clinical characteristics and condition of cancer patients as well as their behavior measured using passively and continuously generated data-streams from smartphone sensors (as in digital phenotyping) with perceived fear of COVID-19 and COVID-19 vaccination status. Methods: 202 patients with different cancer types and undergoing various treatment completed the COVID-19 Fears Questionnaire for Chronic Medical Conditions and their vaccination status was evaluated. Patients’ behavior was monitored using smartphone application that passively and continuously captures high resolution data from personal smartphone sensors. Activity and sociability characteristics were calculated for patients who were monitored for at least two weeks. In total, this sample consisted of 116 patients. The study was conducted between August 2022 and August 2023. Distributions of clinical and demographical parameters between fully vaccinated, partly vaccinated and not vaccinated patients was compared using the Chi2 test. The fear of COVID-19 between the groups was compared using Mann Whitney criteria and Kruskal-Wallis criterion. Trajectories of passively generated data was compared as a function of fear of COVID-19 and COVID-19 vaccination status using local polynomial regression. Results: In total, 202 patients were included in the study. Most patients were fully (71%) or partially (13%) vaccinated and 16% of patients were not vaccinated for COVID-19. Fully vaccinated or not vaccinated patients reported greater fear of COVID-19 than partially vaccinated patients. Fear of COVID-19 was higher in patients being treated with biological therapy. Patients who reported higher fear of COVID-19 spent more time at home, had shorter distance from home and visited less places of interest (POI). Fully or partially vaccinated patients visited more POIs than not vaccinated patients. Meanwhile, fully vaccinated or unvaccinated patients had similar trend of POI and it did not exceed three visits per day during the entire treatment period. Conclusion: Higher perceived fear of COVID-19 was associated with less movement, more time spent at home and less time spent outside of home as well as lower number of visited places. Unvaccinated patients visited less places and were moving less overall during 14-week follow-up as compared to vaccinated patients.